A combined method to estimate wind speed distribution based on integrating the support vector machine with firefly algorithm. Issue 3 (15th October 2015) - Gani, Abdullah; Mohammadi, Kasra; Shamshirband, Shahaboddin; Altameem, Torki A.; Petković, Dalibor; Ch, Sudheer
Abstract : A new hybrid approach by integrating the support vector machine (SVM) with firefly algorithm (FFA) is proposed to estimate shape ( k ) and scale ( c ) parameters of the Weibull distribution function according to previously established analytical methods. The extracted data of two widely successful methods utilized to compute parameters k and c were used as learning and testing information for the SVM‐FFA method. The simulations were performed on both daily and monthly scales to draw further conclusions. The performance of SVM‐FFA method was compared against other existing techniques to demonstrate its efficiency and viability. The results conclusively indicate that SVM‐FFA method provides further precision in the predictions. Nevertheless, for daily estimations, the applicability of proposed method could not be feasible owing to high day‐by‐day fluctuations of parameters k, whereas the results of monthly estimation are completely appealing and precise. In summary, the SVM‐FFA is a highly viable and efficient technique to estimate wind speed distribution on monthly scale. It is expected that the proposed method would be profitable for wind researchers and experts to be used in many practical applications, such as evaluating the wind energy potential and making a proper decision to nominate the optimal wind turbines. © 2015 American Institute of Chemical Engineers Environ Prog, 35: 867–875, 2016